Incidence, Enteropathogenicity and Antibiotic Sensitivity of Vibrio parahaemolyticus from a Brackishwater Culture Pond - S., Sanjeev (Fishery Technology, 2025)
Incidence of Vibrio parahaemolyticus and total bacterial count of water, sediment and prawn (Penaeus monodon) from a brackishwater culture pond situated near Cochin were studied. V.parahaemolyticus count was 460 MPNml"1 in water and in sediment, it was upto 2.4xl04 MPNg-1. V. parahaemolyticus load of prawn harvested from the pond was 2.4xl04 MPNg"1. Water temperature varied from 28.2 to 320C, salinity from 1.83 to 24.58%o and pH from 7.51 to 8.69. 12.4% of V. parahaemolyticus strains were Kanagawa-positive. All the 250 strains were found sensitive towards chloramphenicol, 68.4% were sensitive to gentamycin, 18% were sensitive to tetracyclin and 16.8% to streptomycin. None of the strains was found sensitive towards penicillin and polymyxin-B.